An examination of the legal rights of a surgical patient under the Nigerian laws (2009)
With the passing of the Universal Declaration of Human Rights, 1948 and signing of the International Covenants on Civil and Political Rights, 1966 and the Economic, Social and Cultural Rights, 1966, there has been a global emphasis on human rights. The issue of patients’ rights has also been brought to prominence with the advent of modern technology and the availability (and use) of artificial measures to prolong life; the evolution of legal rights and duties of patients, an increased concern for the rights of the patients, the increase in number of people affected by HIV/Aids, and a growing population of elderly patients. However, apart from those international instruments setting out human rights, most national Constitutions have equally set out fundamental rights of individual. In this category is the Constitution of the Federal Republic of Nigeria, 1999 which sets out fundamental human rights enjoyable by everyone (any patient inclusive) within the territory of the country. Violation of these rights is enforceable in court and the violator may be liable to pay heavy damages and compensation. This article discusses those rights that centre on the relationship of a patient and his/her healthcare providers, specifically, the rights of a surgical patient in relation to his/her medical doctors, nurses, other health personnel and health institutions